KAJIAN TEKNOLOGI DAUR ULANG TIMAH DARI AKI BEKAS YANG RAMAH LINGKUNGAN - Wiharja Wiharja (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Recycling used battery to collect lead (Plumbum) have been executed by communities. This practice has been accepted for generations, and they have not accomplished scientific assessments yet, particularly in term of environmental aspect. In order to create synergy between potential economic and prevent environmental impact of this performance, therefore it is absolutely necessary to manage lead recycling from battery activities. Using appropriate technology could also reduce air pollution of lead dust (Pb particulate) andexcess air.